PENDIDIKAN DAN PEMBELAJARAN (HOME SCHOOLI/\.G) (Suatu Tinjauan Teoritis dan Praktis) - Muhtadi, Ali (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Educational innovation must continues improved, remember still much education problems that have not yet handled properly by conventional method, specially in accomodating difference owned by students from character facet, intellegence, background, physical growth, mental, enthusiasm, talent, learns style etc. Existance of home schooling education model is must countered as a form of educational model alternative and awareness of evocation old fellows of its responsibility to their children education